Hydrogen sulphide as a guard cell network regulator - Pantaleno, Rosario (2020)
Hydrogen sulphide (H2S) is an endogenously produced gasotransmitter that has rapidly emerged as an active signalling component of several plant processes, stomatal movement regulation among them. The guard cells (GCs), pairs of cells that neighbour the stomatal pores, transduce endogenous and environmental signals, through signalling network, to control stomatal pore size. In this complex network, which has become a model system for plant signalling, few highly connected components form a core that links most of the pathways. The evidence summarized in this insight, on the interplay between H2S and different key components of the GC networks, points towards H2S as a regulator of the GC core signalling pathway.